Association between the prognostic nutritional index and early mortality of AML patients after allogeneic HSCT: a retrospective cohort analysis - Tang, Jie; Ran, Feng; Li, Gangping; Jiang, LiQuan; Wang, Li; Wang, Yali; Feng, Yimei; Chen, Xiaoli; Zhang, Xi (Frontiers in Oncology, 2026)
BackgroundAllogeneic hematopoietic stem cell transplantation (Allo-HSCT) is an effective treatment for Acute Myeloid Leukemia (AML). The pre-transplantation Prognostic Nutritional Index (PNI) plays a critical role in determining patient prognosis, however, its correlation with mortality within 180 days after SCT is currently unclear.ObjectiveThis study aimed to investigate the association between PNI and mortality within 180 days among AML patients who underwent HSCT.MethodsWe conducted a cohort study by retrospectively collecting data from AML patients who underwent HSCT. The PNI was calculated and recorded as serum albumin (g/L) + 5 × peripheral blood lymphocyte count (109/L) using pre-transplantation laboratory data. Patients were divided into three groups based on PNI tertiles. A Cox proportional hazards model was employed to explore the nonlinear relationship between PNI and mortality in these patients. The correlation between pre-transplant PNI and hematopoietic reconstitution, as well as complications such as gastrointestinal bleeding, fever, and graft-versus-host disease (GVHD), was also analyzed.ResultsThis retrospective cohort study included 477 adult patients with AML. The mean age of the patients was 37.4 ± 11.8 years, with males accounting for 55.6%. The vast majority (79.5%) of patients received transplants from related donors. Among those patients, 13.2% died within 180 days after transplantation. Patients with PNI T1 (30.2–44.6) had a significantly higher adjusted hazard ratio (HR) for mortality (1.52; 95% confidence intervals (CI), 1.17–1.98; p = 0.002) compared with PNI T2 (44.7–49.1), while PNI T3 (49.2–102.6) did not show increased risk (HR, 1.05; 95% CI, 0.81–1.35; p = 0.732). A PNI threshold of 46 marked a significant decrease in mortality risk with increasing PNI values, suggesting a critical point for nutritional intervention. Above this threshold, PNI showed no further prognostic value, indicating a plateau effect. These findings underscore PNI’s potential in guiding targeted nutritional support to improve post-transplant outcomes.ConclusionsThe PNI exhibits a L-shaped association with 180-day mortality in AML patients post-HSCT, emerging as a significant predictor with a critical threshold identified at PNI 46. Below this threshold, declining PNI values correlate with increased mortality risk, underscoring its clinical utility in driving nutritional interventions to enhance post-transplant survival outcomes.